„Dlaczego chowacie pod klosz wartości, wartości tego świata” - o wartościach i anty wartościach w tekstach zespołu, „Dżem” - Filip, Grażyna; Kuraś, Klaudia (Słowo. Studia językoznawcze, 2015)
The article „Why do you hide the values under the cloche, the values of this world? – values and anti-values in the lyrics of the band Dżem” presents the issue of positive and negative values emphasized by the representatives of rock music. The above-mentioned topic has been undertaken due to the current changes in the axiological hierachies. The axiological methodology applied within this article in order to describe the exemplary data, has been inspired primarily by the terminology and classifications proposed by J. Puzynina. The research has been based on the material in form of ninety-four songs recorded by Dżem in years 1979–2005. The following paper discusses three positive values: freedom, family and acceptance and two anti-values: loneliness and wealth. As a result, the article does not only analyze the aforesaid values, but it also attempts to provide a profile of a typical character delineated in Dżem’s songs.